A randomized controlled trial of a brief behavioral intervention to reduce skin and soft tissue infections among people who inject drugs. (1st April 2021) - Phillips, Kristina T.; Stewart, Catherine; Anderson, Bradley J.; Liebschutz, Jane M.; Herman, Debra S.; Stein, Michael D.
Highlights: We tested a brief intervention (SKIN) for hospitalized people who inject drugs. A two-group RCT (SKIN vs assessment-only) was conducted with 12-months of follow-up. SKIN participants reduced the number of uncleaned skin injections. SKIN participants had fewer skin infections, but differences were not significant. Abstract: Background: People who inject drugs (PWID) are at high risk for skin and soft tissue infections (SSTIs), but few interventions have targeted their reduction. The goal of the current study was to test the effects of a brief skin and needle hygiene behavioral intervention (SKIN) in a two-group randomized controlled trial with 12-month follow-up. Method: PWID (N = 252) were recruited from inpatient hospital units at a single urban medical center site and randomly assigned to an assessment-only (AO) condition or SKIN, which was a two-session intervention that included psychoeducation, behavioral skills demonstrations, and motivational interviewing. Mixed effects generalized linear models assessed the impact of the intervention on frequency of: 1) self-reported SSTIs, 2) uncleaned skin injections, and 3) injection. Results: Participants were 58.3 % male, 59.5 % White, and averaged 38 years of age. SKIN participants had 35 % fewer SSTIs compared to AO (p = .179), a difference of nearly one infection per year. The mean rate of uncleaned skin injections was about 66 % lower (IRR = 0.34, 95 % CI 0.20; 0.59, p < .001) among SKIN participants compared to AO. Almost one-third of participants reported no injection over follow-up and the mean rate of injection during follow-up was about 39 % lower (IRR = 0.61; 95 % CI 0.36; 1.02, p = .058) among persons randomized to SKIN than AO. Conclusions: The SKIN intervention reduced uncleaned skin injections but did not reduce SSTIs significantly more than a control condition. Brief interventions can improve high-risk practices among PWID and lead to clinically meaningful outcomes.